Geochemical study of Cretaceous magmatic rocks in Chuzhou region, low Yangtze River metallogenic belt: implications for petrogenesis and Cu–Au mineralization. Issue 11 (26th October 2018) - Hu, Zilong; Yang, Xiaoyong; Lee, Insung
ABSTRACT: The low Yangtze River metallogenic belt (LYRMB) is one of the most important poly-metal deposit belts in China. The Chuxian, Machang and Shangyaopu intrusions in the LYRMB are intermediate rock series, mainly composed of monzonite and quartz monzonite. In this study, bulk rock major and trace elements, zircon U–Pb dating and Hf isotope were analysed. Five ages have been obtained as (1) Chuxian, 121.8 ± 1.9 and 124.0 ± 1.4 Ma, respectively, (2) Machang intrusion, 123.1 ± 2.0 Ma and (3) Shangyaopu, 126.6 ± 1.8 and 123.4 ± 1.9 Ma, indicating that the regional igneous activity was in Early Cretaceous, being consistent with the massive Yanshanian magmatic events in eastern China. These three intrusions are identified as a high-Mg adakite, most of them showing geochemical features of high Si, high Na and low Sr, which can be interpreted as partial melting of subducted oceanic crust. High Mg# characteristics indicate the magmas reacted with the mantle. The negative zircon ε Hf values of these adakites suggest that the magmas have assimilation of old crustal material, e.g. Archaean continental crust, the basement of the south Tancheng–Lujiang (Tan–Lu) fault. Biotite Ti temperature result (about 700°C) shows that intrusive magma has a relatively low temperature. Petrogenesis and regional Cu–Au mineralization mechanism may be explained by Pacific plate subduction during about 125–180 million years subducted to southwest towards the LYRMB. Magmas formed by partial melting of subducted oceanic crust have systemically high Cu–Au contents, which are conducive to corresponding mineralization. Graphical Abstract: